Dietary exposure assessment of antibiotic residues in chicken meat from selected chicken slaughterhouses in Peninsular Malaysia - Md Rodzi, Marzura (2018)
Dietary intake of significant amounts of antibiotic residue can lead to adverse health effects and also lead to development of antimicrobial resistance in foodborne pathogens. The objectives of this study were to screen the presence of antibiotic residues in slaughtered chickens; to quantitate antibiotic residues concentrations and to estimate dietary intake (EDI) of antibiotic residues for children and adult. Antibiotic residues in a total of 637 slaughtered chicken sample from selected slaughterhouses in Peninsular Malaysia were screened using microbial inhibition test and quantitated with Liquid Chromatography Mass Spectrometry (LC-MS/MS). An exposure assessment was conducted to detect and quantitate tetracycline, sulfonamide and quinolones in slaughtered chickens in Peninsular Malaysia and the results were then applied to calculate the risk estimates using deterministic and probabilistic approaches. The result showed that 17 of 637 (2.7%) samples were positive by screening for antibiotic residues. Majority of the samples detected with tetracyclines residues (82.4%), followed by quinolones (29.4%) and sulfonamides (23.5%). The result from confirmatory method showed a total of 10 (1.6%) samples were positive for tetracyclines, while enrofloxacin was detected below maximum residue limits (MRLs) in one sample, whereas sulphonamide was not detected in any samples. Through deterministic approach, the dietary intake of tetracycline in adult was estimated to be 0.00921 μg/kg bw/day compared to 0.05919 μg/kg bw/day in children. The lower aged children groups (1<y<3 and 4<y<6) had the highest tetracycline intakes compared to the adult group. Exposure dietary intake (EDI) for the children and adults could reach up to 0.2% and 0.1% of the defined acceptable daily intake (ADI), respectively. Based on probabilistic approach, tetracycline residues intake was higher in children (ranged from 0.13779 μg/kg bw/day to 0.33935 μg/kg bw/day) compared to adult (ranged from 0.09002 μg/kg bw/day to 0.4333 μg/kg bw/day). EDI for the children and adults could reach up to 0.5% to 1% and 0.1% to 0.3% of the defined ADI, respectively. The results produced by probabilistic approach were slightly higher compared to deterministic analysis as all possible data provided has been taken into account. Both approaches yielded the estimate risks lower than the ADI for tetracycline at 30 μg/kg bw/day. Based on the ADI limit, the results indicated that the toxicological risk associated to the consuming of chicken was insignificant and could be considered as safe. However, occurrence of high concentration of antibiotic residues in small number of samples still warrant a closer monitoring and management on the use of antibiotics in chicken farms in Peninsular Malaysia. It is crucial for the authorities to instigate policies for a better control of the potential risk of antibiotic residues in foods of animal origin.